Cultivating Democratic Values in ELT Classrooms - Sugiono, Sugiono (International Journal of English Education and Linguistics (IJoEEL), 2024)
Institutions and democratic values come under a global threat, by which there is a pressing need to leverage education as a means of nurturing active, engaged citizens. This qualitative study examines how English language teaching (ELT) can be reimagined to foster democratic values and competencies among learners. Drawing on in-depth interviews and classroom observations across five rural secondary schools in Probolinggo regency, the research explores the perspectives and experiences of ELT educators implementing democratically-oriented curricula and pedagogies. The findings reveal how ELT classrooms integrating critical thinking exercises, intercultural communication activities, and civic engagement projects can empower language learners with the knowledge, skills, and dispositions necessary for effective democratic participation. Implications for teacher training, curriculum design, and ELT policy are discussed, highlighting the transformative potential of language education in advancing democratic principles worldwide